Enhancing Antenatal Care: Evaluating Coverage and Quality in Primary Health Facilities - Abdullah Mohammed Alashhab, Anwar Eid Alruwaili, Maha Saleh Binabdulaziz, Sattam Menwer Alsulami (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Antenatal care plays a crucial role in maternal health services by providing essential information about pregnancy risks and facilitating birth planning, thereby reducing maternal and infant morbidity and mortality. In rural populations access antenatal services through primary health care facilities such as Basic Health Units and Rural Health Centers. This study focuses on evaluating the coverage and quality of antenatal care in primary health care facilities Methods: A combination of quantitative and qualitative methods was employed for data collection. Nine districts were selected using a multistage sampling technique, with 19 public sector primary health care facilities (comprising seventeen Basic Health Units and two Rural Health Centers) randomly chosen from each district. Focus group discussions and in-depth interviews were conducted with clients, providers, and health managers. Results: The study revealed an overall antenatal checkup enrollment rate of 55.9%, with a subsequent visit dropout rate of 32.9%. The quality of services pertaining to assessment, treatment, and counseling was found to be significantly lacking. Factors contributing to low coverage and poor quality included the distant location of facilities, inadequate resources, indifferent staff attitudes, and staff shortages. Additionally, limited client awareness regarding the importance of antenatal care and insufficient self-empowerment for decision-making regarding seeking care were identified as further barriers to optimal coverage. Conclusion: The findings highlight a substantial compromise in both coverage and quality of antenatal care services . Only half of expected pregnancies are enrolled for care, with one-third dropping out during follow-up visits. These results underscore the urgent need for targeted interventions to improve accessibility and enhance the quality of antenatal care services in the region